Angle error compensation in wheel force transducer. (January 2016) - Wang, Dong; Lin, Guoyu; Zhang, Weigong; Jiang, Tao
Highlights: We proposed an angle error compensation method for the WFT. We established the mathematical models of angle error. We demonstrated the algorithm with the simulations and real vehicle test. Abstract: Wheel force transducers (WFTs) have performance characteristics that make them attractive for applications in endurance evaluation of road vehicles, ride and handling optimization, tire development and vehicle dynamics. Since the WFT is mounted on the wheel and rotates with it, the rotational angle of the wheel is indispensable to calculate the real wheel forces. Unfortunately, an angle error caused by the steering of the vehicle will be incorporated into the measurement of the rotational angle, resulting in great error in the wheel force calculation. A new compensation algorithm is proposed in this paper to eliminate this angle error. In this algorithm, the GPS speed has been introduced to modify the measurement of the rotational angle in real time. Simulations with designed vehicle movement are carried out to demonstrate the effectiveness of the compensation algorithm. Furthermore, the results of real vehicle test show that this algorithm can be successfully used in practice to get more reasonable wheel loads.